Recent updates on cancer immunotherapy - Liu, Ming (Precis Clin Med, 2018)
Traditional cancer therapies include surgery, radiation, and chemotherapy, all of which are typically non-specific approaches. Cancer immunotherapy is a type of cancer treatment that helps the immune system fight cancer. Cancer immunotherapy represents a standing example of precision medicine: immune checkpoint inhibitors precisely target the checkpoints; tumor infiltrating lymphocytes, TCR T cells, and CAR T cells precisely kill cancer cells through tumor antigen recognition; and cancer vaccines are made from patient-derived dendritic cells, tumor cell DNA, or RNA, or oncolytic viruses, thus offering a type of personalized medicine. This review will highlight up-to-date advancement in most, if not all, of the immunotherapy strategies.